E-learning policy and technology enhanced flexible curriculum delivery in developing contexts: A Critical Discourse Analysis - Magunje, Caroline; Chigona, Agnes (Critical Studies in Teaching and Learning, 2023)
Most higher education institutions globally have used e-learning policies as a strategy for technology enhanced curriculum delivery. However, few universities in Zimbabwe have e- learning policies, and lack of such documents to guide technology integration leads to inefficiency and hinders provision of effective support. This study highlights the role of e-learning policy through analysis of e-learning documents and statements at a university in Zimbabwe. Using critical discourse analysis, the study unpacks the discourse of e-learning at the university, to reveal underlying assumptions and beliefs of the neoliberal, elitist paradigm, veiled under ‘widening access’ and flexible learning. Contexts, such as the Zimbabwean higher education, sector have very specific needs, which must be considered when formulating e-learning policies to ensure effectiveness of implementation.